2015
DOI: 10.1111/ene.12725
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging abnormalities in photosensitive juvenile myoclonic epilepsy

Abstract: Several microstructural variations between PPR positive and negative JME patients have been identified. Our findings highlight the pivotal role of the thalamus in the pathophysiology of primary generalized seizures and suggest that thalamo-premotor connections are both an essential part of epileptic networks and important in the pathogenesis of photosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Whereas reduced FA has been frequently detected in a broad range of brain disorders, increases in FA as seen here have been reported more rarely. In the thalamus particularly, which is a fiber‐rich structure, increased FA was observed in paroxysmal kinesigenic dyskinesia, presymptomatic Alzheimer's disease, childhood absence epilepsy, or photosensitive juvenile myoclonic epilepsy; this pattern of increased FA could be due to a selective degeneration of white matter fibers, whereas the decreased volume of the thalamus and the accompanying increased mean diffusivity seen at P30 are compatible with decreased cell number in the thalamocortical system. FA changes seen at P56 in the corpus callosum of Grin2a KO mice were apparently not due to increased myelination of white fibers, although we cannot exclude that subtle changes in axon myelination might have escaped detection from immunohistochemistry experiments, especially given that the relative FA increased by about 5% on average in Grin2a KO mice at P56 ().…”
Section: Discussionmentioning
confidence: 98%
“…Whereas reduced FA has been frequently detected in a broad range of brain disorders, increases in FA as seen here have been reported more rarely. In the thalamus particularly, which is a fiber‐rich structure, increased FA was observed in paroxysmal kinesigenic dyskinesia, presymptomatic Alzheimer's disease, childhood absence epilepsy, or photosensitive juvenile myoclonic epilepsy; this pattern of increased FA could be due to a selective degeneration of white matter fibers, whereas the decreased volume of the thalamus and the accompanying increased mean diffusivity seen at P30 are compatible with decreased cell number in the thalamocortical system. FA changes seen at P56 in the corpus callosum of Grin2a KO mice were apparently not due to increased myelination of white fibers, although we cannot exclude that subtle changes in axon myelination might have escaped detection from immunohistochemistry experiments, especially given that the relative FA increased by about 5% on average in Grin2a KO mice at P56 ().…”
Section: Discussionmentioning
confidence: 98%
“…The underlying pathophysiology of JME is not fully understood, and a multifactorial mechanism is likely in most cases . Attempts to discover the cause of JME using brain MRI have been frequently conducted in recent years . Although routine brain MRI with visual inspection is typically normal in patients with JME, subtle structural and functional abnormalities are also well described using advanced imaging analysis techniques such as voxel‐based morphometry, diffusion tensor imaging (DTI), and resting state functional MRI (rs‐fMRI) .…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a group of voxel‐based morphometry studies on a meta‐analysis of gray matter differences between patients with JME and healthy controls have found that the patients with JME have increased gray matter volumes in the medial frontal gyrus and decreased gray matter volumes in the bilateral thalamus . A study using DTI in patients with JME has demonstrated increased fractional anisotropy in the ventromedial thalamus and decreased fractional anisotropy in the lateral geniculate nucleus, compared to healthy controls . Another study investigating the amplitude and spatial distribution of spontaneous low‐frequency oscillations, using analysis of fractional amplitude of low‐frequency fluctuation, in the patients with JME has revealed significant fractional amplitude of low‐frequency fluctuation increases in the bilateral medial thalamus .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of epilepsy has been able to take advantage of the introduction of a number of new drugs with good seizure control and improved adverse event profile [160][161][162][163][164][165][166][167][168]. Status epilepsy remains the most important life-threatening dimension of epilepsy.…”
mentioning
confidence: 99%